Few-layer MoS2 flakes as a hole-selective layer for solution-processed hybrid organic hydrogen-evolving photocathodes. Issue 9 (10th February 2017) - Bellani, Sebastiano; Najafi, Leyla; Capasso, Andrea; Del Rio Castillo, Antonio Esau; Antognazza, Maria Rosa; Bonaccorso, Francesco
Abstract : Solution-processed H2 -evolving hybrid organic PEC cells are boosted by using few-layer p-doped MoS2 flakes as an efficient atomic-thick hole-selective layer. Abstract : High-efficiency organic photocathodes, based on a regioregular poly(3-hexylthiophene) and phenyl-C61-butyric acid methyl ester (rr-P3HT:PCBM) bulk heterojunction sandwiched between charge-selective layers, are emerging as efficient and low-cost devices for solar hydrogen production by water splitting. Nevertheless, stability issues of the materials used as charge-selective layers are hampering the realization of long-lasting photoelectrodes, pointing out the need to investigate novel and stable materials. Here, we propose MoS2 flakes, produced by Li-aided exfoliation of the bulk counterpart, as an efficient atomic-thick hole-selective layer for rr-P3HT:PCBM-based photocathodes. We carried out p-type chemical doping to tune on-demand the MoS2 Fermi level in order to match the highest occupied molecular orbital level of the rr-P3HT, thus easing the hole collection at the electrode. The as-prepared p-doped MoS2 -based photocathodes reached a photocurrent of 1.21 mA cm −2 at 0 V vs. RHE, a positive onset potential of 0.56 V vs. RHE and a power-saved figure of merit of 0.43%, showing a 6.1-fold increase with respect to pristine MoS2 -based photocathodes, under simulated 1 sun illumination. Operational activity of the photocathodes over time and under 1 sun illumination revealed a progressive stabilization of the photocurrents at 0.49 mA cm −2 at 0 V vs. RHE. These results pave the way towards the exploitation of layered crystals as efficiency-boosters for scalable hybrid organic H2 -evolving photoelectrochemical cells.